EU action in the fight against doping - Andreu, J. (1999)
Paper on the IEC Doping Conference, 17 - 18 June 1999 in Barcelona. "The limits of sport: doping". 1. Introduction 2. The European Council of Vienna 3. The EU in the World Conference of Lausanne 4. The Working Group Commission/Member states